Modeling Asymmetric Volatility Connectedness and Spillover Dynamics in Emerging Forex Markets Through the Lens of a TVP-VAR Framework - Singh, Raj Kumar; Sharma, Tarun; Singh, Yashvardhan; Kumar, Ajay; Kumar, Sunil (Indian Journal of Finance, 2025)
Purpose : This article investigated asymmetric volatility connectedness and spillover dynamics in emerging forex markets, emphasizing BRICS countries, amid recent geopolitical and trade-tariff conflicts. Methodology : The analysis employed the recently introduced TVP-VAR framework by Antonakakis et al. (2020) on daily exchange rate data from April 2015 to March 2025, sourced from Investing.com. Findings : The study uncovered several key insights. Based on realized variance, the total connectedness index stood at 24.02, reflecting weak connectedness with South Africa and Brazil as net transmitters and Russia, China, and India as net receivers. Consistent with prior evidence, connectedness intensified in crises and weakened during stable periods. The spillover asymmetric measure highlighted the dominance of positive volatility, where RS+ was revealed to be low and RS– was suggested to have weak connectedness. Conversely, cross-market connectedness, estimated at 33.87, within a 2N × 2N dimensional framework, confirmed the dominance of bad volatility. Additionally, network-connectedness analysis identified Russia’s pivotal position in transmitting volatility across BRICS forex markets. Implications : The study contributed to the literature by applying advanced methodology to emerging economies. For investors, it provided actionable insights for portfolio and risk management strategies. For policymakers, the weak connectedness underscored the need to strengthen economic and financial integration to advance the de-dollarization agenda and enhance regional market resilience. Originality : This study offered a novel perspective on volatility spillover dynamics in emerging foreign exchange markets and introduced a unique framework for ranking spillover indices.